Managing the Welsh Government Data Access Panel: A Multidisciplinary Approach to Ethical Data Use - Albiston, Carmel; Helliwell, Kathryn (International Journal of Population Data Science, 2026)
The Welsh Government Data Access Panel plays a critical role in enabling secure, ethical, and legally compliant access to Welsh Government microdata for research purposes. This session will explore how we manage applications to use these sensitive datasets, ensuring that projects deliver public value while safeguarding privacy and data integrity. Our approach brings together experts in data security, legal compliance, data protection, and IT from across the organisation to workshop strategic issues. These include defining the breadth of project approvals that are both legally and ethically appropriate for our context, and balancing innovation with risk management. By convening this multidisciplinary panel, we create a robust governance framework that supports transparency and accountability in decision-making. The process also incorporates individuals with specialist knowledge of the relevant datasets, ensuring that subject matter expertise informs decision-making alongside considerations of data security, legal compliance, and ethical standards. A key focus of the session will be how Welsh Government microdata can be integrated with other sources in a way that respects legal and ethical boundaries while unlocking research potential. We will share insights from recent workshops where panel members collaborated to address complex questions around data minimisation, consent, and safeguarding public trust. Attendees will gain practical understanding of how governance structures can enable responsible data sharing, and how collaborative approaches can resolve tensions between research ambition and regulatory obligations. This work is central to advancing population data science and ensuring that administrative data can inform evidence-based policy for the benefit of citizens.